Knowledge and perception about stroke among an Australian urban population - Levi Christopher; Heller Richard F; Sug Yoon Sung; Wiggers John (BMC, 2001)
Abstract Background The aim of the study was to measure knowledge about the symptoms, prevalence and natural history of stroke; the level of concern about having a stroke; understanding of the possibilities for preventing stroke, and the relationship between age, sex, country of origin, educational level, income, self-reported risk factors, and the above factors. Methods A random sample of households was selected from an electronic telephone directory in Newcastle and Lake Macquarie area of New South Wales, Australia, between 10 September and 13 October 1999. Within each household the person who was between 18 and 80 years of age and who had the next birthday was eligible to participate in the study (1325 households were eligible). The response rate was 62%. Results The most common symptoms of stroke listed by respondents were "Sudden difficulty of speaking, understanding or reading" identified by 60.1% of the respondents, and "paralysis on one side of body" identified by 42.0% of the respondents. The level of knowledge of the prevalence of a stroke, full recovery after the stroke, and death from stroke was low and generally overestimated. 69.9% of the respondents considered strokes as being either moderately or totally preventable. There were few predictors of knowledge. Conclusion The study suggests that educational strategies may be required to improve knowledge about a wide range of issues concerning stroke in the community, as a prelude to developing preventive programmes.